Trauma and Insecurity in Kimetsu no Yaiba: A Cognitive Psychology Study - Alifiah Riyanti (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
This study examines how trauma and insecurity influence the cognitive processes and decision-making of characters in Kimetsu no Yaiba, using Aaron Beck’s cognitive psychology as the primary framework. Focusing on Giyuu Tomioka and Akaza, this research explores how their past experiences shape cognitive distortions, maladaptive schemas, and coping mechanisms. Data were gathered through close reading of the manga’s visual and narrative elements, then assessed using selected items from BDI-II and BAI to identify traits of trauma and insecurity. The findings reveal that trauma and insecurity profoundly shape the characters’ cognition and decisions. Giyuu’s unresolved guilt over his sister’s and Sabito’s deaths leads to self-doubt, emotional withdrawal, and a coping style marked by avoidance and social isolation, despite his position as the Water Pillar. Akaza’s life as Hakuji shows compounded grief from losing his father, Keizou, and Koyuki, resulting in intense rage and psychological decompensation. This culminates in dissociative amnesia after he becomes a demon, erasing memories tied to his trauma yet leaving an unconscious drive for strength to protect against further loss. Across the characters, trauma emerges as a catalyst for either destructive decisions or reluctant perseverance, shaping their journeys toward heroism or tragic downfall. This study highlights how unresolved sorrow and insecurity distort perception and guide choices, enriching the literary portrayal of guilt, vulnerability, resilience, and the silent struggles beneath outward strength.